Gender Issues: a Critical Discourse on Articles in Online Media Magdalene. Co - Astuti, Widi; Budiman, Dwi Aji; Saragih, Rasianna Br; Widiastuti, Wahyu (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study aims to determine how the discourse formation of articles on the issue of violence against women in the online media Magdalene.co which appeared from June to December 2021. This research uses descriptive qualitative research methods, the research subject is the author of articles on violence against women in Magdalene.co media and the object of research is articles on violence against women. The data collection techniques used in the research are documentation and interviews with parties related to the research theme. The data analysis method uses the Van Dijk model which consists of three dimensions, namely Text, Social Congnition, and Social Context. The data validity test uses triangulation techniques. The results of the research at the text level show that the discourse in the article on violence against women in the online media Magdalene.co. in the content of the article emphasizes the condition of women as victims of violence and some sentences show how the perpetrators of violence behave. Judging from the level of social congnition, Magdalene.co journalists in their articles emphasize the condition of women as victims of violence. Judging from the level of social context, information about women's harassment will always be a taboo issue for society. This issue will continue to be discussed in the community considering the number of victims of violence against women is quite large, so this will continue to be an issue that will be published in the mass media.